2016
DOI: 10.1155/2016/8940850
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Açaí (Euterpe oleracea Mart.) against Rotenone In Vitro Exposure

Abstract: Neuropsychiatric diseases, such as bipolar disorder (BD) and schizophrenia (SCZ), have a very complex pathophysiology. Several current studies describe an association between psychiatric illness and mitochondrial dysfunction and consequent cellular modifications, including lipid, protein, and DNA damage, caused by cellular oxidative stress. Euterpe oleracea (açaí) is a powerful antioxidant fruit. Açaí is an Amazonian palm fruit primarily found in the lowlands of the Amazonian rainforest, particularly in the fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 63 publications
1
36
0
2
Order By: Relevance
“…Diets rich in polyphenolic compounds and in soluble/insoluble fibers have been correlated to the maintenance of good health in humans . The Passiflora seeds show good levels of these category of compounds, but have been discarded by the pulp agroindustry in Brazil .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diets rich in polyphenolic compounds and in soluble/insoluble fibers have been correlated to the maintenance of good health in humans . The Passiflora seeds show good levels of these category of compounds, but have been discarded by the pulp agroindustry in Brazil .…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Diets rich in polyphenolic compounds and in soluble/insoluble fibers have been correlated to the maintenance of good health in humans. 18,19 The Passiflora seeds show good levels of these category of compounds, but have been discarded by the pulp agroindustry in Brazil. 20 Passiflora setacea stands out for its high content of polyphenolic compounds, which are mainly concentrated in the seeds, 26 times higher than that found in the commercial passion fruit P. edulis Sims [P. setacea seeds presents 5018 mg catechin equivalent/100 g, higher than P. edulis seeds (193 mg catechin equivalent/100 g), according to Vieira (2013)], 20 so it could be a good ingredient to enhance nectar phytochemical quality, and to reduce waste in the pulp agroindustry.…”
Section: Introductionmentioning
confidence: 99%
“…EO extract and isolated metabolites such as (-)-epigallocatechin-3-gallate, cyaniding glucoside, cyaniding rutinoside caused loss of thioflavin T (ThT) fluorescence, with cyaniding glucoside also disrupting Aβ 1–42 fibril and aggregate morphology [ 86 ]. A study by Machado et al [ 87 ] suggested the use of EO as an alternative therapy for the treatment of bipolar disorder associated with mitochondrial dysfunction and cell oxidative stress. Exposure to EO extract increased enzyme activity of the mitochondrial complex I, amounts of proteins and, mainly, protein overexpression in mitochondrial complex I Q module subunits NDUFS7 and NDUFS8, and reduced levels of ROS and cellular lipid peroxidation.…”
Section: Biological Eo Activities: Application In the Prevention Amentioning
confidence: 99%
“…In Tierstudien und in-vitro werden bereits Substanzen zur Behandlung von psychiatrischen Erkrankungen durch pharmakologische Beeinflussung der Atmungskette erprobt [25][26][27]. Im Mausmodell konnten anxiolytische Effekte nach Gabe eines mitochondrienspezifischen Antioxidans erzielt werden [28].…”
Section: Somatische Untersuchungenunclassified